INTERFERENSI BAHASA PADA PENULISAN PAPAN NAMA USAHA - Riska, Clara; Jupitasari, Mellisa; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to describe forms of foreign and regional language interference in writing business name boards in Sungai Raya District, Kubu Raya Regency. Analyzing data related to forms of foreign and regional language interference, as well as the factors that cause interference. This research method is a qualitative descriptive method. The data sources for this research are business nameplates and business owners who have nameplates in Sungai Raya District. Data collection techniques through observation, interviews and recording. This research produced 40 data on forms of foreign and regional language interference which included 21 foreign language vocabularies, 7 regional language vocabularies, and 2 foreign and regional language vocabularies. Foreign language morphological interference was not found, regional language morphological interference amounted to 3 data. Foreign language syntactic interference totaling 7 data includes foreign phrase patterns (M-D). Regional language syntactic interference was not found. Factors causing interference are (1) bilingualism, (2) low loyalty of the recipient's language, (3) Prestige source language and language style, (4) carrying over native language habits.